2016
DOI: 10.1016/j.lindif.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Coping with University Education: The relationships of Time Management Behaviour and Work Engagement with the Five Factor Model Aspects

Abstract: It is posted here for your personal use. No further distribution is permitted. AbstractWe examined the construct validity of time management behaviour and work engagement, defined as a positive work-related state of mind. Two-hundred and eighty-one participants completed the Time Management Behaviour Scale, the Utrecht Work Engagement ScaleStudent Version, and the Big Five Aspect Scales. Linear regression analyses revealed that Time Management Behaviour was positively predicted by the Conscientiousness aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
4
20
0
3
Order By: Relevance
“…Industriousness (partialling Orderliness), Openness, and Intellect appear to be robust predictors of components of work engagement (vigor, dedication, and absorption;Bakker, Schaufeli, Leiter, & Taris, 2008;Douglas, Bore, & Munro, 2016;Woods & Sofat, 2013). Intellect (distinct from Openness) also predicts more effortful cognitive engagement during a difficult cognitive task (Smillie, Varsavsky, Avery, & Perry, 2016), whereas Openness (distinct from Intellect) has been linked with deeper engagement in abstract art (Fayn, Tiliopoulos, & MacCann, 2015).…”
Section: Personality Traits and (P)erma Well-beingmentioning
confidence: 99%
“…Industriousness (partialling Orderliness), Openness, and Intellect appear to be robust predictors of components of work engagement (vigor, dedication, and absorption;Bakker, Schaufeli, Leiter, & Taris, 2008;Douglas, Bore, & Munro, 2016;Woods & Sofat, 2013). Intellect (distinct from Openness) also predicts more effortful cognitive engagement during a difficult cognitive task (Smillie, Varsavsky, Avery, & Perry, 2016), whereas Openness (distinct from Intellect) has been linked with deeper engagement in abstract art (Fayn, Tiliopoulos, & MacCann, 2015).…”
Section: Personality Traits and (P)erma Well-beingmentioning
confidence: 99%
“…The PERMA‐Profiler operationalizes the engagement dimension in terms of absorption, feeling excited and interested in things, and losing track of time while doing things you enjoy. Industriousness (partialing Orderliness), Openness, and Intellect appear to be robust predictors of components of work engagement (vigor, dedication, and absorption; Bakker, Schaufeli, Leiter, & Taris, ; Douglas, Bore, & Munro, ; Woods & Sofat, ). Intellect (distinct from Openness) also predicts more effortful cognitive engagement during a difficult cognitive task (Smillie, Varsavsky, Avery, & Perry, ), whereas Openness (distinct from Intellect) has been linked with deeper engagement in abstract art (Fayn, Tiliopoulos, & MacCann, ).…”
Section: Personality Traits and Three Taxonomies Of Well‐beingmentioning
confidence: 99%
“…A study of psychology students in Australia found that conscientious students tend to have better time management scores and engagement scores [15]. It also found that students with higher engagement scores were more likely to be "quick" learners, whereas students with higher time management scores were likely to be "consistent" learners.…”
Section: Procrastination and Timely Approachesmentioning
confidence: 99%